Effect of Temperature on the Efficiency of the Thermal Cell - M. Sarhan, Waleed; N. Alkhateeb, Ahmed; D. Omran, Kareem; H. Hussein, Falah (Asian Journal of Chemistry, 2010)
The operational temperature of the laboratory thermal cell was found to be within the range 455–460ºC, at which the alloy, CaLi2 was formed, which led to the oxidation of the calcium anode and the release of the electrons. The effect of different temperatures upon the efficiency of the thermal cell at different times has been studied. The results show that 460ºC is the most appropriate temperature, where a regular discharge took place beside the generation of the most stable voltage. This result is explained as being due to the fast assimilation of the reactants. Concerning the assembled thermal cell, the operation temperature was determined to be 455–460ºC, which is identical with that found with the laboratory thermal cell. An obvious increase of the voltage to become 2.3 V, which was regularly formed, has been observed. Moreover, studying the effect of the same temperatures, used with the laboratory thermal cell, that is 400, 460 and 520ºC, has been carried out. It revealed that 460ºC represents the optimum temperature for the assembled thermal cell to work with the highest efficiency, where the molten salt, depolarizer and the binder were LiCl-KCl, CaCrO4 and SiO2, respectively.